Evaluation of a Stroke Protocol Using Computed Tomography Angiography for the Evaluation of Acute Ischemic Stroke Patients - W. Schrock, Jon; Day, Robert; Morris, Peter; Reed, Steven; Ferguson, Robert; Hanna, Joseph (Journal of Neurological Research And Therapy, 2017)
Objectives: Computed tomography angiography (CTA) provides early assessment of cerebral vasculature in ED patients presenting with Acute Ischemic Stroke (AIS). Prior studies using 4 row detector CT scanners have suggested that results may be used to determine who receives thrombolytics (tPA). We sought to evaluate the rate of normal CTA and the use of tPA in AIS patients with and without blockages using modern CT technology. Patients and Methods: We conducted a retrospective cohort study of all code stroke patients presenting to our ED over a 3 year period. Inclusion criteria included an ED and neurology diagnosis of AIS with a CTA performed at presentation. All patients had a NIHSS score recorded at presentation and underwent imaging using a 64 row detector scanner with 50cc of non-ionic contrast. Demographic, imaging, and clinical data were collected. Modified Rankin Scores (mRS) were assigned at hospital discharge. Good clinical outcome was defined as a mRS of 0-2. Data are reported as frequencies and medians with interquartile ranges (IQR) as appropriate. Rates of tPA use were evaluated using χ2 testing. Rates of good outcomes were evaluated using odds ratios. Results: A total of 205 subjects met inclusion for analysis of which 103 (50%) were male and 109 (54%) had no blockage on CTA. The median NIHSS score and mortality rates were 14 (IQR 8-19), 14 (14%) with CTA blockage, and 4 (IQR 2-7), 2 (2%) for those without. Of those AIS with a blockage on CTA 46 (48%) were treated with tPA including 29 who were treated with intra-arterial therapy as well while only 13 (13%) of patients without a blockage were treated with tPA. Post tPA bleeding occurred in 12 (13%) patients with blockage on CTA and in 0 patients without blockage. Use of tPA was significantly more frequent in patients with a blockage on CTA, P <0.001. Conclusion: More than half of our AIS patients presenting through our ED have no blockage on CTA. Inter-rater reliability among neuroradiologists evaluating for large vessel occlusion appears to be very good. Patients with AIS and no blockage on CTA have less severe strokes and are less likely to receive tPA. Given the new guidelines recommending endovascular treatment for AIS we expect more emergency departments to begin performing CTA.
Keywords: Stroke; computed tomography; computed tomography angiography